An anisotropic damage formulation for composite materials based on a gradient-enhanced approach: Formulation and implementation at small strain. (1st October 2020) - Yin, Bo; Zreid, Imadeddin; Lin, Guoyu; Bhashyam, Grama; Kaliske, Michael
Abstract: Classical gradient enhanced damage models have been intensively studied and demonstrated to provide reliable predictions of structural failure. Singularities due to local softening have been properly overcome to obtain stable and converged numerical solutions. As expected, mesh-dependency has been avoided as well. Motivated by experiments, several damage patterns of fiber reinforced material in practical applications are comprehensively characterized as anisotropic properties, which are governed by both the elastic response and the damage behavior simultaneously. The present work describes an anisotropic damage evolution by incorporating a gradient enhanced model for composite materials. Three independent non-local variables are introduced to govern the damage evolution along three orthogonal directions, which subsequently lead to independent degradation of the components in material stress and the consistent tangent. The constitutive law of the coupled problem is derived and, subsequently, is implemented into the context of the Finite Element framework. To appropriately demonstrate the capabilities of this approach, representative benchmark problems are studied and compared to corresponding experiments. Consequently, related findings and potential perspectives are summarized to provide further context for future applications.